Myocarditis in Humans and in Experimental Animal Models - Błyszczuk, Przemysław (Frontiers in Cardiovascular Medicine, 2019)
Myocarditis is defined as an inflammation of the cardiac muscle. In humans, various infectious and non-infectious triggers induce myocarditis with a broad spectrum of histological presentations and clinical symptoms of the disease. Myocarditis often resolves spontaneously, but some patients develop heart failure and require organ transplantation. The need to understand cellular and molecular mechanisms of inflammatory heart diseases led to the development of mouse models for experimental myocarditis. It has been shown that pathogenic agents inducing myocarditis in humans can often trigger the disease in mice. Due to multiple etiologies of inflammatory heart diseases in humans, a number of different experimental approaches have been developed to induce myocarditis in mice. Accordingly, experimental myocarditis in mice can be induced by infection with cardiotropic agents, such as coxsackievirus B3 and protozoan parasite Trypanosoma cruzi or by activating autoimmune responses against heart-specific antigens. In certain models, myocarditis is followed by the phenotype of dilated cardiomyopathy and the end stage of heart failure. This review describes the most commonly used mouse models of experimental myocarditis with a focus on the role of the innate and adaptive immune systems in induction and progression of the disease. The review discusses also advantages and limitations of individual mouse models in the context of the clinical manifestation and the course of the disease in humans. Finally, animal-free alternatives in myocarditis research are outlined.